2016
DOI: 10.4014/jmb.1602.02063
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Fluoroquinolone Antibiotic Resistance Mechanism of Salmonella enterica Isolates

Abstract: Quinolone-resistant Salmonella strains were isolated from patient samples, and several quinolone-sensitive strains were used to analyze mutations in the quinolone resistance-determining region (QRDR) of gyrA, gyrB, parC, and parE and to screen for plasmid-mediated quinolone resistance. Among the 21 strains that showed resistance to nalidixic acid and ciprofloxacin (MIC 0.125-2.0 μg/ml), 17 strains had a mutation in QRDR codon 87 of gyrA, and 3 strains had a single mutation (Ser83 → Phe). Another cause of resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 23 publications
(26 reference statements)
2
17
0
2
Order By: Relevance
“…Previously, qnrA , qnrB , qnrS , and aac(6')-Ib-cr plasmid-mediated resistance genes were reported in quinolone-resistant, non-typhoidal Salmonella [36]. The Qnr protein induces resistance to nalidixic acid, thereby decreasing or limiting susceptibility to fluoroquinolones [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, qnrA , qnrB , qnrS , and aac(6')-Ib-cr plasmid-mediated resistance genes were reported in quinolone-resistant, non-typhoidal Salmonella [36]. The Qnr protein induces resistance to nalidixic acid, thereby decreasing or limiting susceptibility to fluoroquinolones [31].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Asai et al [34] could detect qnrS among 0.08% of the S. enterica isolates of food-producing animals while Kim et al [33] reported qnrB4 and qnrS1 in 3.2% of the isolates from poultry. Prevalence of qnr genes in S. enterica human clinical isolates was also reported as low in recent studies [3536]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCR amplification, DNA sequencing, and sequence analysis PCR assays were conducted targeting QRDRs of the gyrA, gyrB, parC, and parE genes with primer pairs as previously reported [17]. The genomic DNA was extracted using the QIAGEN Midi Kit (Qiagen, Hilden, Germany).…”
Section: Bacterial Strains and Antimicrobial Susceptibility Testingmentioning
confidence: 99%
“…To investigate the molecular basis of high FQ resistance in the C. jejuni isolates, we analyzed the full gene sequences encoding the DNA gyrase subunits (gyrA and gyrB) (9,10) and the topoisomerase IV subunits (parC and parE) (11,12), which are known targets of FQ, the regulatory protein CmeR, and the sequence of the promoter region of cmeABC, which encodes an efflux pump (13,14), by DNA sequencing as previously described (15,16). The MICs of ciprofloxacin against the 39 isolates which represent different sequence variants were tested according to CLSI guidelines (17,28).…”
mentioning
confidence: 99%